Experimental Study of the Characteristic Changes of Coal Resistivity during the Gas Adsorption/Desorption Process. (21st October 2018) - Feng, Zengchao; Wang, Chen; Dong, Dong; Zhao, Dong; Zhou, Dong
Abstract : To study the influence of gas adsorption-desorption on the resistivity of coal, the resistivity changes in conditions of continuous adsorption/desorption and isovolumetric adsorption/desorption were tested by high-precision resistance measurement, and the relationship between coal resistivity and gas content was investigated. The results show that gas adsorption/desorption has obvious effects on the resistivity of coal. Similar behavior was observed both in continuous adsorption/desorption and in isovolumetric adsorption/desorption experiments. The coal resistivity decreased gradually at the very beginning and then tended to stabilize as the gas adsorption capacity increased; in the process of gas desorption, the resistivity demonstrated a linear relationship with gas content. When comparing resistivities for the different adsorption modes, it was found that, for the same gas content in each mode, the resistivity change in the isovolumetric adsorption experiment was more obvious than in the continuous adsorption experiment. Also, the coal resistivity in the isovolumetric experiment differed further from the original figure when the desorption ended. The results are significant for predicting gas content in the coal mining process.